Systematic Literature Review : Evaluasi Kebijakan Program Bantuan Langsung Tunai Dana Desa (BLT-DD) Berdasarkan Model Evaluasi Kebijakan William N Dunn - Dhea Ayu Fitria; Weni Rosdiana (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
The Village Fund Direct Cash Assistance Program (BLT-DD) is a social protection instrument designed to help low-income families meet their basic needs. However, its implementation often faces challenges such as targeting inaccuracies, limited data, and varying administrative capacity at the village level. This study aims to evaluate the implementation of BLT-DD using William N. Dunn’s six policy evaluation criteria through a Systematic Literature Review (SLR) approach, covering effectiveness, efficiency, equity, responsiveness, conceptual alignment, and implementation. The findings indicate that BLT-DD is fairly effective in helping households maintain consumption, yet its effectiveness and adequacy remain constrained by the amount of assistance and the quality of data collection. Program efficiency and responsiveness are relatively good in villages with sufficient governance capacity, while equity emerges as the weakest aspect due to inaccurate data verification. Conceptually, BLT-DD aligns with the needs of low-income communities, but implementation accuracy still requires reinforcement. Furthermore, the study highlights the need for more systematic monitoring mechanisms, cross-sectoral data integration, and administrative training for village officials to enhance service quality. Overall, BLT-DD provides valuable support but requires improvements in governance and data systems to optimize outcomes, including regular evaluation strategies and refinement of supporting regulations.